Land use and agricultural change dynamics in SAT watersheds of southern India - Ahmed, I.M.; Gumma, Murali K.; Kumar, S.; Craufurd, Peter Q.; Rafi, I.M.; Haileslassie, Amare (2016)
Impact of dynamic land use and land cover changes on the livelihood of local communities and ecosystem services is a major concern. This is particularly evident in most dryland agricultural systems in South Asia. We study land use/land cover (LULC) changes over the last two decades in a watershed (9589 ha) located in semi-arid eco-region in South India (Anantapuram district) using Landsat and IRS imagery. We captured additional data through field observations and focused group discussions. The high resolution 30 m data and the spectral matching techniques (SMTs) provided accuracy of 91–100% for various land use classes and 80–95% for the rice and groundnut areas. The watershed studied has undergone significant land use changes between 1988 and 2012. Diminishing size and number of surface water bodies, and contrastingly increased areas under irrigation clearly explain that the system has evolved significantly towards groundwater-irrigated groundnut production. Such changes could be beneficial in the short run, but if the groundwater withdrawal is without sufficient recharge, the long-term consequences on livelihoods could be negative. The water scarcity could be aggravated under the climate change. The construction of checkdams and dugout ponds to recharge groundwater is a potential solution to enhance recharge.